The Benefit of English - Dwi Meisyitah Ananda (Jurnal Pengabdian Masyarakat Kesosi, 2022)
The ability to speak English is an obligation in the era of globalization. However, there are still many phenomena where English proficiency is still considered low, especially for the class of society who still considers English a difficulty. Community service is carried out to invite the community back about English and things that help to improve English language skills. The results show that the importance of English has been fully realized but the obstacle lies in the approach used to improve English language skills. An introduction to the importance of the number of vocabularies is introduced to help improve English language skills. This is important to do as a form of step that can be used to improve and invite the community (especially school children who live in the community) to determine the right steps.